Parents' perspectives on the bilingual program in the region of Madrid - Zahra Chaieberras (Centro Universitario Cardenal Cisneros, 2019)
This article attempts to identify parent perspectives on Content and Language Integrated Learning in Madrid. It presents an empirical study that was carried out in Compulsory Secondary Education in the region of Madrid. The study seeks to identify the perceptions of parents as regards the bilingual project and their children's achievements learning a second language. The data are obtained from a qualitative and quantitative questionnaire to examine: students' use, competence and development of English in class; methodology; materials and resources; evaluation; training and information; mobility; and finally, improvement and motivation towards learning English. Statistical techniques are also included to show if there are statically significant differences concerning the parental variables.